Improving environmental performance and related costs in a public organization through initial environmental review : case study - Helsinki Police Department - Charoenpornpimonkul, Tida (2017)
The purpose of this study is to explore what the Helsinki Police Department could do to improve its overall environmental performance and related costs from the perspective of sustainable development. A research project on this topic was carried out and became the groundwork of this thesis. The two reviewed theoretical concepts were: (1) initial environmental review and (2) sustainable environmental direction and practices.